2008
DOI: 10.1002/0471143030.cb0420s39
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing Protease Activity in Living Cells: From Two Dimensions to Four Dimensions

Abstract: Proteolytic degradation of extracellular matrix (ECM) components by cells is an important metabolic activity as cells grow, remodel, and migrate through the ECM. The ability to analyze ECM degradation can be valuable in the study of developmental processes as well as pathologies, such as cancer. In this unit we describe an in vitro live cell–based method to image and quantitatively measure the degradation of ECM components by live cells. Cells are grown in the presence of fluorescent dye‐quenched protein subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(80 citation statements)
references
References 14 publications
0
80
0
Order By: Relevance
“…We have established methods for quantifying the fluorescent cleavage products that result from DQ-collagen degradation 2,3 . We normalize degradation products throughout the entire 3D volume of the MAME cocultures on a per cell basis by labeling and counting cell nuclei.…”
Section: Representative Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have established methods for quantifying the fluorescent cleavage products that result from DQ-collagen degradation 2,3 . We normalize degradation products throughout the entire 3D volume of the MAME cocultures on a per cell basis by labeling and counting cell nuclei.…”
Section: Representative Resultsmentioning
confidence: 99%
“…We normalize degradation products throughout the entire 3D volume of the MAME cocultures on a per cell basis by labeling and counting cell nuclei. Furthermore, we can localize the degradation to extracellular and intracellular compartments and quantify the total, intracellular and extracellular degradation products as we have described previously 2 . The green fluorescence in Figures 2 and 3 represents cleavage products of the two DQ-collagen substrates.…”
Section: Representative Resultsmentioning
confidence: 99%
“…This collagen allows for the microscopic analysis of proteolysis because it has an excessive amount of fluorescent dyes conjugated to it which causes a quenching effect. After it has been enzymatically degraded, the quenching is reduced and the local area becomes fluorescent (Jedeszko et al, 2008). Therefore, areas of DQ collagen fluorescence indicate collagenase proteolytic activity, which would be mediated by many of the invadopodia-associated MMP enzymes, including MMP-2.…”
Section: Mechanical Stimulation Increases the Expression And Activitymentioning
confidence: 99%
“…Using a live cell imaging assay for proteolysis developed in our laboratory [19][20][21][22], we have shown that co-culturing macrophages with breast carcinoma cells increases degradation of the basement membrane protein type IV collagen and that this degradation is reduced by inhibitors of MMPs and CTSB [21]. Therefore, our aim in the present study was to determine how breast cancer cells modulate expression and activity of the proteases CTSB, MMP-2 and MMP-9 in human monocytes.…”
Section: Introductionmentioning
confidence: 96%